DELTA STATE BUSINESS CENTRE OPERATOR'S PERCEPTION OF INFORMATION COMMUNICATION TECHNOLOGY COMPETENCIES REQUIRED FOR SUCCESS (NAU Journal of Technology and Vocational Education, 2024)
This study sought to determine the perception of Delta State business centre operators ofICT competencies needed for success in their business. Two research questions hasguided the study. The study was a survey research and the area of study was Delta State.The population of the study consisted of 624 business centre operators registered with theministry of commerce in Delta State. The sample for the study consisted of 375 businesscentre operators randomly selected from the population of the study. Structuredquestionnaire with 43 items used for data collection, for the study. The reliability of theinstrument was determine by the use of split half method using spearman rank order ofcorrelation while the coefficient was further computed using the spearman brown'prophecy formula, t-test statistical tool was used for analysis of the hypotheses at 0.05level of significance. Findings revealed that word processing and spread sheetcompetencies are perceived as highly required for successful operation of business centre.It was recommended among others that curriculum planners should incorporate thevarious competencies as perceived by Delta State business centre operators in ICTprogrammes both at the secondary and tertiary levels of education and that businesscentre operators who are deficient in the perceived competencies in word processing andspreadsheet should endeavour to acquire further training in order to achieve the requiredcompetencies for successful business centre operation.
Keywords: Business Centre operators, word processing, spreadsheet analysis